The Effect of Work Attachment on the Performance of Freelance Daily Employees at PT X Semarang - Muhammad Taufiq Febriyanto; Sutarto Wijono (International Journal Labs, 2023)
In the current new normal era, economic conditions are growing rapidly and advancing. This makes various companies in Indonesia need to make various adaptations and are required to continue to innovate and develop in order to be able to compete with other companies to dominate the market. This study aims to determine the effect of work attachment on the performance of freelancer employees at PT. X Semarang. The research method used in this study was quantitative using a sample of 52 employees. Sampling technique in this study, the author used a probability simple random sampling technique. Data collection in this study used the Utrecht Work Engagement Scale (UWES) compiled by Schafeuli and the Job Performance Scale compiled by Koopmans, et al. Based on the results of data analysis, it was found that work attachment has a positive and significant influence on employee performance by obtaining an F value of 19.804 with a significance level of 0.000 (< 0.05). Work attachment has an influence of 28.4% on employee performance. Thus, the more employee work attachment increases, the more employee performance increases.